Quasi-periodic pulsations in solar flares: a key diagnostic of energy release on the Sun - Inglis, Andrew (2023)
To fully understand solar flare energy release we require flare-focused rapid cadence multi-wavelength solar imaging, with sufficient sensitivity and dynamic range to observe quasi-periodic pulsations (QPPs). This must be combined with multidisciplinary funding and initiatives that will narrow the gap between numerical models of this fundamental phenomenon and observations.